Green potential of tall buildings in Vietnam case study : Institute of Agriculture / Nguyen Hoang Tuan - Tuan, Nguyen Hoang (2012)
The construction industry in Vietnam is developing and there are more and more high-rise buildings built with different types such as: residential buildings, commercial buildings and more complicated high-rise buildings. However, most of these new and under-construction buildings were not designed with respect to the local climate nor were they environmental friendly. This paper presents a case study of energy efficient design for the Institute of Agriculture in Vietnam as an underlying research to evaluate potential energy savings and LEED green building rating points. First, the study analyses local weather data to find the potential for efficient design improvement. Then, two widely used and accepted Ecotect and Equest building simulation software were run with typical meteorological year (TMY) weather input data. The results of integrated design show that the building can utilize up to 50% of recycled construction materials in the local regions reduce water use up to 65% and produce 63% on-site renewable energy. The integrated design focuses on optimum orientation, glazing, green roof, insulation, shading design, daylight dimming control, on-site renewable energy and water reduction.